Mindfulness-Based Cognitive Therapy’s Effect on the Symptoms of Currently Depressed Individuals: A Systematic Review of Existing Meta-Analytic Evidence - Liu, Jenny J. W.; Ein, Natalie; Fung, Kenneth (Canadian Journal of Counselling and Psychotherapy, 2019)
Mindfulness-based therapies have been the recipient of both widespread attention and critique. Meta-analyses have begun to examine the efficacy of specific forms of therapies and in specific populations. However, there have been mixed findings on the effects of mindfulness-based cognitive therapy (MBCT) on acute depressive symptoms. This systematic review will focus on the examination of 6 meta-analyses on MBCT in depressed populations published between 2007 and 2016. The goal of this review is to examine the efficacy of MBCT studies in these meta-analyses for individuals with current depression. Special attention will be paid to the experimental rigour in the quality of studies published. Results of the systematic review found that depressive symptoms significantly decreased following MBCT in individuals with current episodes of depression. Heterogeneities in study design and assessment might have contributed to the mixed findings in previous meta-analyses. These findings support the efficacy of MBCT in acute depression, and implications are discussed.